Kajian etnosains dalam ritual belaq tangkel pada masyarakat suku sasak sebagai sumber belajar IPA - Husnul Mukti; B Fitri Rahmawati; M. Marzuki Marzuki (Universitas Hamzanwadi, 2022)
The Sasak community has a diversity of customs, arts, and culture as well as traditions that have been passed down from generation to generation, including the Belaq Tangkel tradition which is part of the ritual during the first pregnancy. This study aims to find the concept of science in the ritual of belaq tangkel in the tradition of the Sasak tribe that can be implemented in learning. This research is an ethnographic study. Data were collected through various literature studies, field observations, and interviews with informants who understand the implementation of the Belaq Tangkel ritual in the traditions of the Sasak people. The results of this study indicate that in the Sasak community, pregnancy is considered a gift (paice) given by God to a family. Therefore, the phases of pregnancy are greeted with certain rituals which are a form of gratitude for being given this gift. One of the rituals performed is the Belaq Tangkel ritual. This ritual is carried out when the womb enters the age of 7 months. The Belaq Tangkel (breaking coconut) ritual is a ritual to ask God Almighty, so that the mother will be facilitated in the birthing process and the child will become a pious and pious child like water and the contents of a clean and white coconut. This ritual tradition is a tradition passed down from generation to generation from the ancestors which is believed to be a ritual to honor the child in the womb and is a deposit that must be guarded and protected and given love by both parents. The Belaq Tangkel tradition is carried out in two stages. The stages of the ritual are reconstructed from the original knowledge of the community into scientific knowledge that has the potential to be used as a science learning resource.